A STRATEGIC DESIGN LOOK AT EDUCATION CHALLENGES IN A PANDEMIC BRAZILIAN CONTEXT - Jaqueline Freitas Comparin; Cristiane Ramos; Karine de Mello Freire (Mix Sustentável, 2022)
By increasing the social gap between students in private and public schools, the pandemic crisis has aggravated existing social problems, exposing the inequalities in Brazilian society and revealing that their consequences do not affect everyone in the same manner. Therefore, this study aims to discuss the relevance of Strategic Design as an agent of transformation through seeding strategy, envisioning social innovation in education. The research ensues from an inductive approach of exploratory nature, the collection of secondary data on the impacts of the COVID-19 pandemic on education, and the works of Ezio Manzini, Anna Meroni, and Francesco Zurlo. It also analyzes solutions already in place, referring to social projects aimed at equity in vulnerable communities. To conclude, this study presents four axes that can be the starting point to disseminate social innovation seeds aiming at constructing innovative models of social work that may reflect on a fairer and more inclusive world.